ANALISIS GAYA BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPA KELAS V SD TAMBAKREJO 01 SEMARANG - Savita Rizky Maulida; Widya Kusumaningsih; Aryo Andri Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this research is to describe the various learning styles of students in science learning for Class V SD Tambakrejo 01 Semarang. Learning styles that suit students are one of the keys to students' success in learning. This study uses a descriptive qualitative approach. The research subjects were fifth grade students at SD Tambakrejo 01 Semarang. The data collection technique used in this study is through the stages of observation, interviews, and documentation. Based on the results of observations made, in the learning process of fifth grade students at SD Tambakrejo 01 there are different characteristics in understanding the material. The results of this study indicate that there are differences in learning styles in students in science learning class V SD Tambakrejo 01 which includes visual learning styles, auditory learning styles, and kinesthetic learning styles.